P80 Divergent guidelines regarding methotrexate prescribing in the UK: time for hepatologists to provide direction?. (28th September 2020) - Turner, Lucy; Veysey, Martin; Hutchinson, John; Millson, Charles
Abstract : Introduction: Low dose methotrexate (MTX), an effective treatment for immune-mediated diseases, has been used by multiple specialities since the 1960s. Historically, MTX-induced hepatotoxicity dictated its potential use; only being advocated in patients with 'life-ruining' disease and regular liver biopsies were mandatory. 1 Guidelines have been divergent across various specialities since 1987, and this persists today. 2–4 Aim: To compare current guidelines regarding MTX prescribing, monitoring and action in the face of presumed hepatotoxicity. Methods: The archives of professional bodies and associations in rheumatology, dermatology and gastroenterology were searched for guidance pertaining to the use of methotrexate, dating back to 1950, within the UK, Europe and America. Results: A total of 17 guidelines related to MTX monitoring were published between 1972 and 2019 by dermatologists, rheumatologists and gastroenterologists. Guidelines differed across specialties to this day in regard to baseline investigations, monitoring and action required on liver blood test abnormality. The most recent of these are demonstrated in table 1 . Discussion: Divergent guidelines regarding low dose MTX, particularly in relation to its apparent hepatotoxicity, have persisted for decades. Liver blood tests are a poor indicator of liver dysfunction and the advent of non-invasive measures of liver fibrosis provide a potential alternative. Hepatologists have stopped short of clear advice and guidance in this area. We have developed an algorithm for patients commencing MTX and receiving this drug long-term, which we hope will provide some consistency. References: Roenigk HH, Jr., Maibach HI, Weinstein GD. Use of Methotrexate in Psoriasis. Archives of Dermatology 1972;105 (3):363–5. Ledingham J, Gullick N, Irving K, Gorodkin R, Aris M, Burke J, et al . BSR and BHPR guideline for the prescription and monitoring of non-biologic disease-modifying anti-rheumatic drugs. Rheumatology (Oxford) . 2017;56 (6):865-8. Warren RB, Weatherhead SC, Smith CH, Exton LS, Mohd Mustapa MF, Kirby B, et al . British Association of Dermatologists' guidelines for the safe and effective prescribing of methotrexate for skin disease 2016. Br J Dermatol . 2016;175 (1):23–44. Biancone L, Annese V, Ardizzone S, Armuzzi A, Calabrese E, Caprioli F, et al . Safety of treatments for inflammatory bowel disease: Clinical practice guidelines of the Italian Group for the Study of Inflammatory Bowel Disease (IG-IBD). Digestive and Liver Disease 2017;49 (4):338–58.